Peran dan Fungsi Yayasan At-Thoharoh dalam Mengembangkan Keagamaan Masyarakat di Nagori Manik Maraja - Muhammad Iqbal; Muhammad Kamal Akbar Javan; Niken Sastri Nurunnihal; Nurchayanti Nurcahyanti; Rizki Kurnia Ningsih; Siti Fatimah; Wardah Khumairah Manurung; Winda Sari Sinaga; Yustika Widya Sazlina (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study aims to find out how the role of the At-Thoharoh Manik Maraja Foundation in managing madrasas, especially in achieving. In addition, this study also wants to know how the function of the foundation, especially in the religious field of madrasas managed by the foundation. Foundations have an important role in people's lives, namely helping people to improve their welfare through education. In addition, the existence of a foundation can help achieve community goals in the social field, both humanitarian and religious. A foundation may earn profits by conducting various businesses, but the profits obtained may only be used for social purposes, not for personal interests. This study uses a qualitative approach. The results of the study indicate that the role of the Darul Irfan foundation in providing education in At-Thoharoh is quite good, although not optimal. The function of fostering the foundation has been carried out, especially in religious guidance, managerial guidance to the head and also financial management. In addition to coaching, the foundation also helps in resolving conflicts that occur between individuals and between units/foundations. The Foundation already has a clear mechanism for conflict resolution.